The pursuit of quality in grounded theory - Charmaz, Kathy; Thornberg, Robert (Qualitative research in psychology, 2021)
This article introduces grounded theory and places this method in its historical context when 1960s quantitative researchers wielded harsh criticisms of qualitative research. The originators of grounded theory, sociologists Glaser and Strauss, sought to defend the quality of qualitative research and argued that grounded theory increased its quality by providing a method of theory construction. Our major foci include: (1) introducing the logic of grounded theory, with emphasis on how researchers can use it to construct theory, (2) detailing criteria for quality in the major forms of grounded theory advocated by Glaser and Strauss and augmented by Glaser, Strauss and Corbin and refined by Corbin, and Charmaz and (3) providing an analysis of how constructivist grounded theorists Thornberg, Halldin, Bolmsjö and Petersson attended to the interviewing process, coding, and developing their theoretical concept of double victimizing. Students and researchers new to the method can use our concluding guidelines as a checklist to assess the quality of their constructivist grounded theory research.